Number theory, trace formulas, and discrete groups : symposium in honor of Atle Selberg, Oslo, Norway, July 14-21, 1987 - Aubert, Karl Egil; Bombieri, Enrico, 1940-; Goldfeld, D. (Academic Press, 1989)
Number Theory, Trace Formulas and Discrete Groups.